Plasticity of Streptomyces coelicolor Membrane Composition Under Different Growth Conditions and During Development - Sandoval-Calderón, Mario; Nguyen, Don D.; Kapono, Clifford A.; Herron, Paul; Dorrestein, Pieter C.; Sohlenkamp, Christian (Frontiers in Microbiology, 2015)
Streptomyces coelicolor is a model actinomycete that is well known for the diversity of its secondary metabolism and its complex life cycle. As a soil inhabitant, it is exposed to heterogeneous and frequently changing environmental circumstances. In the present work, we studied the effect of diverse growth conditions and phosphate depletion on its lipid profile and the relationship between membrane lipid composition and development in S. coelicolor. The lipid profile from cultures grown on solid media, which is closer to the natural habitat of this microorganism, does not resemble the previously reported lipid composition from liquid grown cultures of S. coelicolor. Wide variations were also observed across different media, growth phases, and developmental stages indicating active membrane remodeling. Ornithine lipids (OL) are phosphorus-free polar lipids that were accumulated mainly during sporulation stages, but were also major components of the membrane under phosphorus limitation. In contrast, phosphatidylethanolamine, which had been reported as one of the major polar lipids in the genus Streptomyces, is almost absent under these conditions. We identified one of the genes responsible for the synthesis of OL (SCO0921) and found that its inactivation causes the absence of OL, precocious morphological development and actinorhodin production. Our observations indicate a remarkable plasticity of the membrane composition in this bacterial species, reveal a higher metabolic complexity than expected, and suggest a relationship between cytoplasmic membrane components and the differentiation programs in S. coelicolor.